On the importance of the humanities in fostering pupils' positive attitude to their studies - Rajeckas , V. (Psichologija, 1971)
One of the basic problems of Soviet school in carrying out universal secondary education consists in fostering pupils' positive attitude to their studies. The studies of the humanities, first of all, literature, history and social science should serve this purpose as these subjects form the basis of ideological education at the secondary school. The article points out that the contents of the humanities and their connection with life are of decisive importance in fostering in children a disposition to their studies. The development of their disposition to work is mostly determined by teaching methods and proper organization of the training process. The author concludes that the formation of pupils' convictions, their disposition to work, and of their attitudes towards society and towards themselves can be considerably affected by properly organized studies of the humanities.
Keywords: humanities; positive attitude to the studies